2022
DOI: 10.1109/tem.2020.3023707
|View full text |Cite
|
Sign up to set email alerts
|

A New Pythagorean Fuzzy Based Decision Framework for Assessing Healthcare Waste Treatment

Abstract: Suitable management and Treatment of Healthcare Waste (HCW) has become a key issue due to its potential risk to human health and the environment, predominantly in emerging nations. The selection of an optimal HCW treatment (HCWT) option is a complicated Multi-Criteria Decision-Making (MCDM) problem that includes several incompatible qualitative and quantitative attributes. This study presents an extended MCDM methodology for assessing and choosing the HCWT options using Pythagorean fuzzy Stepwise Weight Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…In the MCDM process, various criteria weighting methods have been developed in the literature (Suh et al 2019 ; Mishra et al 2020a ; Rani et al 2020c ). The criteria weight computation procedures are classified as objective weight and subjective weight (Peng 2019 ).…”
Section: Related Workmentioning
confidence: 99%
“…In the MCDM process, various criteria weighting methods have been developed in the literature (Suh et al 2019 ; Mishra et al 2020a ; Rani et al 2020c ). The criteria weight computation procedures are classified as objective weight and subjective weight (Peng 2019 ).…”
Section: Related Workmentioning
confidence: 99%
“…Health and economic considerations for the disposal of environment polluting materials, such as solid wastes, has attracted growing research attention, especially during recent years ( Chowdhury et al, 2019 , Rani et al, 2020 ). Considering the undeniably destructive consequences of applying improper waste collection and disposal systems in both rural and urban area, this is definitely an inevitable part of public healthcare and prevention that must be acknowledged before treatment strategies are pursued ( Darmian et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dahooie et al ( 2018 ) developed the SWARA (Step-wise Weight Assessment Ratio Analysis) with Grey ARAS model to deal with IT personnel assessment issue. Rani et al ( 2020b ) made use of the SWARA-ARAS framework to assess the healthcare waste treating method Rostamzadeh et al ( 2020 ) initiated a fuzzy ARAS model and its relevance in MCDM problems. Recently, Mishra et al ( 2021a ) suggested an integrated ARAS method to evaluate and prioritize the locations for the EVCS.…”
Section: Literature Reviewmentioning
confidence: 99%